Protocol for a feasibility study to inform the development of a multicentre randomised controlled trial of asthma-tailored pulmonary rehabilitation versus usual care for individuals with severe asthma. Issue 3 (23rd March 2016) - Majd, Sally; Apps, Lindsay D; Hudson, Nicky; Hewitt, Stacey; Eglinton, Elizabeth; Murphy, Anna; Bradding, Peter; Singh, Sally; Green, Ruth; Evans, Rachael
Abstract : Introduction: Pulmonary rehabilitation with core components of exercise training and multiprofessional education is an integral part of the management of patients with chronic lung disease. International guidelines for individuals with asthma recommend exercise as exercise improves symptoms, indices of cardiopulmonary efficiency, health status and psychosocial outcome. However, there is little published evidence evaluating safety and acceptability of exercise training for individuals with severe asthma and there are concerns regarding exercise-induced asthma. We propose a feasibility study for a multicentre randomised controlled trial (RCT) of asthma-tailored pulmonary rehabilitation (asthma-tailored PR) versus usual care in individuals with severe asthma. Methods and analysis: The study will be conducted in three stages. Adults with severe asthma will be included if they have persistent symptoms despite being at step 4 or 5 of the British Thoracic Society guidelines. Stage 1: semistructured interviews will be used in a sample of 20–30 individuals with severe asthma to understand the experience and attitudes of this population towards exercise. Stage 2: eight focus groups of at least six healthcare professionals involved in the care of patients with severe asthma will be conducted to understand their attitudes towards exercise for this population. Stage 3: a small-scale RCT of the proposed multicentre RCT of asthma-tailored PR versus usual care for individuals with severe asthma will be conducted. The primary outcome measures will be recruitment, retention and adverse event rates. Semistructured interviews with participants of stage 3 will be used to identify further barriers or facilitators to participation in PR and the trial. Thematic analysis will be used for the interpretation of all interviews. Ethics and dissemination: The study results will inform the design of a larger multicentre RCT. The National Research Ethics Service Committee East Midland approved the study protocol. Trial registration number: ISRCTN96143888.